Non-Applicability of the Law in the Canonical Legal Order - Dzierżon, Ginter (Prawo Kanoniczne, 2025)
In the presented study, the author reflects on the issue of the non-applicability of a statute within the canonical legal order. Already in the ‘Introduction,’ he observed–and later demonstrated–that the principles functioning within the system (such as the impossibility of observing the law, legal doubt, and epikeia) and institutions (privilege, dispensation) reflect the unique nature of ecclesiastical law, which is rooted in the phenomenon of the Church. He argued that the authority of faith is the source of the binding force of the law. The specific principles and institutions articulated by the author, which exempt individuals from adhering to the law, are closely connected with the supreme principle of the canonical system, according to which the supreme law is the salvation of souls (can. 1752).